Highly magnetic iron carbide nanoparticles as effective T(2) contrast agents - Huang, Guoming; Hu, Juan; Zhang, Hui; Zhou, Zijian; Chi, Xiaoqin; Gao, Jinhao (Nanoscale, 2014)
This paper reports that iron carbide nanoparticles with high air-stability and strong saturation magnetization can serve as effective T2 contrast agents for magnetic resonance imaging. Fe5C2 nanoparticles (~20 nm in diameter) exhibit strong contrast enhancement with an r2 value of 283.2 mM(-1) S(-1), which is about twice as high as that of spherical Fe3O4 nanoparticles (~140.9 mM(-1) S(-1)). In vivo experiments demonstrate that Fe5C2 nanoparticles are able to produce much more significant MRI contrast enhancement than conventional Fe3O4 nanoparticles in living subjects, which holds great promise in biomedical applications.